Extraction of bioactive molecules from sea waste - CHIEFA, FRANCESCO (Università degli studi di Ferrara, 2025)
This thesis focuses on the extraction of bioactive molecules from sea waste, aiming to explore the potential of these natural resources for applications in food products and pharmaceutical sectors. The study explored different perspectives on the topic, including nutritional characterizing, food security, innovative technologies and biodiversity. First, we evaluated the effect of two immersion times (24 h and 18 h) on the growth, mortality, biochemical, and elemental composition of Ostrea edulis (O. edulis) and Magallana (Crassostrea) gigas (M. gigas), farmed using off-bottom methods in the “Valli di Comacchio” (Ferrara) from January to July 2023. While M. gigas showed no differences in final mass, O. edulis was affected by immersion time. Shell length was greater with 24 h immersion, but mortality increased with 18 h immersion only in O. edulis. Growth rates were highest in May for oysters immersed 24 h, likely due to warmer temperatures and better food availability. Biochemical analysis showed O. edulis reared for 18 h had more saturated fatty acids, probably due to higher palmitic acid. Shell elemental composition varied, except for calcium and manganese. However, immersion time had limited effects on the edible part of the oysters. Both species reached commercial size in 6–7 months, confirming “Valli di Comacchio” as a promising farming site. The study also highlights the importance of biodiversity conservation, particularly the protection of native species O. edulis. Further research focused on O. edulis quality across seasons. Nutritional and antioxidant properties, carotenoids, and contaminants were analyzed in winter, summer, and autumn. Proteins, EPA, DHA, and amino acids reached the maximum in winter, while oleic acid, lysine, and magnesium were highest in summer. Lipids and carbohydrates were more abundant in autumn. Toxic metal levels were higher in winter, while polycyclic aromatic hydrocarbons appeared in summer and autumn. Monitoring these factors is essential for improving farming techniques and ...